(untitled) (Eurasian Journal of Philology Science and Education, 2025)
The modern education system is undergoing a period of significant transformation, driven by the shift in educational paradigms and the rapid development of digital technologies. Extralinguistic factors are actively penetrating various spheres of public life, including education, revealing the weaknesses of traditional approaches and necessitating a rethinking of existing teaching models. It has become evident that former teaching methods are insufficient for preparing functionally literate, creative, and adaptable graduates capable of thriving in a rapidly changing world. In this context, didactics faces the urgent task of identifying new, effective educational strategies that foster the development of students’ research, communicative, critical, and creative competencies. The integration of information and communication technologies (ICT) and artificial intelligence (AI) into the learning process is becoming increasingly important, demanding that educators continuously update their methods, tools, and instructional techniques. This article analyzes current trends in domestic and international linguodidactics, particularly those related to the shift toward a new educational paradigm and the active use of digital technologies. Special attention is given to the potential of multimedia platforms, AI tools, and digital resources in teaching Russian. The goal of the study is to explore and analyze existing methods of teaching Russian with the integration of ICT and AI, with a focus on the development of research, communication, critical, and creative skills in students. The methodological basis of the research includes the works of leading domestic and international didactic scholars (A.V. Khutorskoy, N.N. Khan, Sh. Kolumbayeva, K.K. Zhampeisova, among others). The main results include the development of methods for teaching Russian, such as algorithms for project-based learning. The findings have high practical significance for online and blended learning and can be used in training programs for school teachers and university instructors. Keywords: linguodidactics, heuristic approach, interactivity, mobile education, Information and Communication Technologies, AI systems.